Profile of Clients & HIV positive patients attending the ICTC of a tertiary care center of Bihar: A situational analysis - Ayub, Arshad; Singh, Geetika; Ahmad, Shamshad; Shekhar, Saket; Palariya, Bhojraj; Rathore, Amita; Kumar, Pragya; Agarwal, Neeraj (Indian Journal of Community Health, 2021)
Background: The services provided in an ICTC help in awareness about HIV and help the clients to undergo HIV test in a comfortable and confidential environment. Periodical evaluation of counseling, testing, and referral services is mandatory to find out any existing deficits and barriers of all functions of ICTCs. Objectives: To study the socio-demographic profile of ICTC attendees and to find out sero-positivity of these clients. Methods: The present study was carried out among ICTC attendees in the ICTC unit, at All India Institute of Medical Sciences of Patna district. A retrospective collection of data from available records of all clients who attended ICTC of our hospital between January 2019 and December 2019 was carried out after approval from institutional research and ethics committee. Results: A total of 28876 clients were tested during January-December 2019 and among them all (100%) of tests were provider initiated. Out of the total attendees, 223 (0.77%) were found to be positive. It was also observed that the number of clients attending the ICTC has increased every month. Conclusion: It shows a high illiteracy and high spouse positive rate among the reactive cases. The young age group was found to be affected more and it definitely raises a cocern.